Avaliação hematológica e bioquímica do sangue efluente esplênico em pacientes esquistossomáticos submetidos a esplenectomia - Kelly Cristine de Lacerda Rodrigues (2012)
INTRODUCTION: The spleen is one of the most vascularised organs of the body, with a blood flow of 350 liters/day. It performs important functions, including haematopoiesis, cell purification, and blood cell storage. In presence of schistosomatic portal hypertension, stasis and blood cell storage may occur due to presinusoidal portal hypertension, often causing enlargement of the spleen and cytopenia. The ligature of the splenic artery, associated to venous drainage during splenectomy, leads to a reduction in the volume of the spleen during the operation, with infusion of splenic blood into the systemic blood flow. An increase in the haematological values can be observed in the immediate post-operative period of splenectomies performed on schistosomatic patients. The role of the blood leaving the spleen in these changes is still unknown. AIM: To verify the haematological and biochemical characteristics of effluent blood from the spleen in schistosomatic splenomegaly and evaluate its influence on the rise in haematological values after a splenectomy. METHOD: The present research studied 20 patients who underwent surgical treatment for schistosomatic portal hypertension. The patients underwent clinical exams and pre-operative anamnesis. Blood samples were collected to perform haematological and biochemical exams (haemogram, coagulogram, bilirubins, and albumin) in the splenic vein (intraoperative) and in the peripheral blood (immediate pre- and post-operative periods). The dimensions and the weight of the spleen were evaluated as well. RESULTS: All these patients presented splenomegaly and thrombocytopenia during the pre-operative period. The splenic blood demonstrated greater values of red blood cells, haemoglobin, haematocrit and platelets, as well as the overall count of leukocytes, neutrophils, lymphocytes, monocytes, eosinophils, and basophils, and also presented reduction in the laboratory parameters of coagulation in comparison with the pre-operative peripheral blood. In the postoperative period, the leukocytes and their neutrophilic component enhanced when compared with their values in the splenic blood effluent. Otherwise the basophils, eosinophils and lymphocytes presented lower values when compared with their values in the splenic blood effluent. The albumin values proved to be lower during the post-operative period as compared to the pre-operative period and to the splenic blood. The direct bilirubin presented higher values in the post-operative period as compared to the pre-operative period and to the splenic blood. The value of the indirect bilirubin in the postoperative peripheral blood was lower than the one found in the splenic blood. CONCLUSIONS: The haematological and biochemical values of the effluent blood from the spleen were greater than those found in the peripheral blood when in the presence of schistosomatic splenomegaly. However, this splenic effluent is not enough to rise the haematological values found after splenectomy.